Whole Genome Analysis of African G12P[6] and G12P[8] Rotaviruses Provides Evidence of Porcine-Human Reassortment at NSP2, NSP3, and NSP4 - Mokoena, Fortunate; Esona, Mathew Dioh; Seheri, Luyanda Mapaseka; Nyaga, Martin Munene; Magagula, Nonkululelo Bonakele; Mukaratirwa, Arnold; Mulindwa, Augustine; Abebe, Almaz; Boula, Angeline; Tsolenyanu, Enyonam; Simwaka, Julia; Rakau, Kebareng Giliking; et al. (Frontiers in Microbiology, 2021)
Group A rotaviruses (RVA) represent the most common cause of pediatric gastroenteritis in children <5 years, worldwide. There has been an increase in global detection and reported cases of acute gastroenteritis caused by RVA genotype G12 strains, particularly in Africa. This study sought to characterize the genomic relationship between African G12 strains and determine the possible origin of these strains. Whole genome sequencing of 34 RVA G12P[6] and G12P[8] strains detected from the continent including southern (South Africa, Zambia, Zimbabwe), eastern (Ethiopia, Uganda), central (Cameroon), and western (Togo) African regions, were sequenced using the Ion Torrent PGM method. The majority of the strains possessed a Wa-like backbone with consensus genotype constellation of G12-P[6]/P[8]-I1-R1-C1-M1-A1-N1-T1-E1-H1, while a single strain from Ethiopia displayed a DS-1-like genetic constellation of G12-P[6]-I2-R2-C2-M2-A2-N2-T2-E2-H2. In addition, three Ethiopian and one South African strains exhibited a genotype 2 reassortment of the NSP3 gene, with genetic constellation of G12-P[8]-I1-R1-C1-M1-A1-N1-T2-E1-H1. Overall, 10 gene segments (VP1–VP4, VP6, and NSP1–NSP5) of African G12 strains were determined to be genetically related to cognate gene sequences from globally circulating human Wa-like G12, G9, and G1 strains with nucleotide (amino acid) identities in the range of 94.1–99.9% (96.5–100%), 88.5–98.5% (93–99.1%), and 89.8–99.0% (88.7–100%), respectively. Phylogenetic analysis showed that the Ethiopian G12P[6] possessing a DS-1-like backbone consistently clustered with G2P[4] strains from Senegal and G3P[6] from Ethiopia with the VP1, VP2, VP6, and NSP1–NSP4 genes. Notably, the NSP2, NSP3, and NSP4 of most of the study strains exhibited the closest relationship with porcine strains suggesting the occurrence of reassortment between human and porcine strains. Our results add to the understanding of potential roles that interspecies transmission play in generating human rotavirus diversity through reassortment events and provide insights into the evolutionary dynamics of G12 strains spreading across selected sub-Saharan Africa regions.